Argumentation With the People of the Book (Ahlul-Kitab) in Surahs Baqarah,AL-Imran,Nisa and Ma'idah:An Analytical Study - Muhammad Kamal -Deen Bello
Argumentation is one of plenty methods of evidencing and launching fact and truth that the Qur'an embarks upon Under the Qur’anic studies, four major and distinctive terms are used to give such meaning; Jadal, Mira ', Muhajjah and Hiwar. Out of the four terms, only two are basically for argumentation; Jadal and Muhajjat while the other two have other meanings on their own besides argumentation and they are used for other things, apart from argumentation in the Qur’an. Argumentation is meant and involves presentation of proofs and evidences. The term is used mostly to iron out some issues with the people of the Book (ahlul-Kitab) in the Qur'an. Argumentation generally is surrounded by some wrong notions, misperceptions and misconceptions, such as subjecting the meaning of argument to quarrel, conflict and war that this thesis wants to look at. The misperception should be corrected, especially at this age that Islam is subjected and said to be the religion of violence and terrorism. Argument being a subject and method of &pression is very fragile and delicate to handle that, if it is properly taken care , it can go out of control and eventually lead to conflict. That is why, some principles and guidelines are laid down by scholars and understood from the Qur'an to guide against such bad occurrence. Argumentation, for proper identification and understanding of course in the Qur'an, its nature, features, types, components will be discussed in details in this work. Generally, in the Qur’an and particularly, in the four chapters studied in the work, there are series of argumentation between Allah and the People of the Book over theological, social and political issues that can probably be the remedies and solutions to religious crises as a problem that the world is facing today, to ensure peace and harmony that we are its quest in Nigeria and Islamic/third world countries in particular and the whole world in general. The method applied here is to critically and analytically assess the Qur’anic argumentative verses Qur’an with the people of the Book over such religious, social and political issues, with the hope that the three Abrahamic religions (Jewish, Christianity and Islam) that claim to believe in oneness of God (Allah) can successively live and speak in one voice without any hitch, difficulty and misunderstanding as brothers in state or nation or universe, if the areas of similarity and disparity are well spelt out and disparity are well spelt out and identified to act upon. However, four Qur’anic chapters are chosen and stipulated as a case study of this research. They are Baqarah, ‘Al-Imran, an-Nisa and al-Ma’idah respectively. The most common argumentative methodology that the holy Qur’an applies here, among others, is repetition for emphasis and evidencing sake. That is why, critical study of the chapter will now tell that two or more verses are revealed against each topic of discussion or theme of argumentation in the Qur’an, as examples of that will be seen in the four chapters studied here.